Correction: Perceptions About Climate Change in the Brazilian Civil Defense Sector - Marchezini, Victor [UNESP]; Londe, Luciana Resende [UNESP]; Loose, Eloisa Beling; Saito, Silvia Midori; Marengo, José A. [UNESP] (Springer Nature, 2022)
The second author’s name was incorrectly captured in the published article. The original article has been corrected.
Correction: Perceptions About Climate Change in the Brazilian Civil Defense Sector (International Journal of Disaster Risk Science, (2022), 13, 5, (664-674), 10.1007/s13753-022-00444-z)